A Q‐band 4‐bit active phase shifter using 0.13 μm CMOS technology. Issue 11 (26th August 2013) - Kim, Ji‐Hoon; Lee, Jong‐Wook
ABSTRACT A four‐bit phase shifter has been designed and fabricated for millimeter‐wave CMOS phase array systems. Instead of using the conventional approach in which lossy switches are used for different phase path selections, we realize phase shifting by summing two quadratures having variable amplitude. Phase shifting is performed in 22.5° steps by using two variable gain amplifiers optimized for a wide phase‐control range. The realized active phase shifter achieves the measured root‐mean‐square (rms) phase error of <11.5° over frequencies from 39 to 42 GHz. The power consumption of the active phase shifter is 238 mW from a 2.4 V supply voltage. A three‐stage cascode gain amplifier is also designed to improve the overall gain of the phase shifter. The gain amplifier achieves a peak gain of 11.5 dB at 39 GHz with power consumption of 53 mW. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2676–2680, 2013